VESTIBULAR NEURITIS AS THE CAUSE OF SYSTEMIC VERTIGO - K. A. Demina; P. S. Nikitenko (SINAPS LLC, 2017)
The Vestibular Neuritis is often mistakenly diagnosed pathology manifested by a sudden acute systemic dizziness, nausea, vomiting, unsteadiness when walking and peripheral nystagmus. The Vestibular Neuritis often occurs under the guise of different diseases - migraine, Meniere's disease, acute disorders of cerebral circulation and others. The vestibular Neuritis is a quite rare pathology, which may cause diagnostic difficulties for physicians of different specialties. As the diagnosis of "vestibular neuritis" is primarily a "diagnosis of exclusion", it is necessary to know peculiarities of clinical picture, course and differential diagnosis with other similar netalogue. The diagnosis of the disease requires the joint and coordinated work of medical specialists: neurologists, ENT, specialists of functional and laboratory diagnostics and laboratory services. Due to the low awareness of this disease doctors of different specialties often make mistakes in diagnosis and treatment. The article presents a clinical case of development of the vestibular Neuritis under the guise of ischemic stroke in the vertebral-basilar pool as an example of the difficulties of differential diagnosis in clinical practice. On the example of a clinical case the course of the disease and possible complications that can occur during this nosology are considered.